Effects of Locally Delivered Morin Hydrate on Iodoacetate-induced Temporomandibular Joint Osteoarthritis in Rats - Abdelhameed, Abdelrahman Mohamed Galal; Hani, Said Mahmoud Mohamed; Soliman, Ahmed Mohamed Mohamed (Brazilian Dental Science, 2020)
Objectives: morin hydrate has been reported to possess many beneficial pharmacological potentialities including antioxidant and anti-osteoarthritic effects. The antiosteoarthritic properties of locally administrated morin have not been investigated. The objective of this study is to evaluate the locally delivered morin on the temporomandibular joint osteoarthritis in rat. Materials and methods: thirty young adult female Sprague Dawley rats were randomly arranged into three groups; control, osteoarthritis and osteoarthritis with morin. Both the iodoacetate for osteoarthritis induction and morin hydrate therapy were delivered unilaterally via intra-articular route. Results: morin reduced osteoarthritis manifestations with prominent thickening of both condylar fibrous layer and articular disc accompanied with discal cells hypertrophy that ultimately acquired chondrocytes features. The condylar cartilage matrix showed enhancement of extracellular matrix production with morin administration. Discussion: the present study has elucidated antiosteoarthritic effect of intraarticular injection of morin hydrate. Although morin has managed to prevent the propagation and advancing some of the recorded osteoarthritic manifestations; however, it showed some failure in managing others. The administration of morin hydrate modulated the structure of the joint rather than restore it back to its typical configuration. Conclusion: the morin hydrate administration to osteoarthritic animals showed relieve in some of osteoarthritic features and modulated the structure of some joint components to compensate the unhandled manifestations. KEYWORDS Iodoacetate; Morin; Osteoarthritis; OARSI Score; Temporomandibular joint.